A cross-sectional study on BMI, anemia, and quality of life in children with sickle cell disease - Chavhan, Shrinal Raghunath; Patil, Sonali; Lalan, Riddhi Hanish; Narlawar, Uday; J. S., Anupama (International Journal Of Community Medicine And Public Health, 2025)
Background: Sickle cell disease (SCD), particularly the homozygous HbSS pattern, is a chronic hematologic condition that significantly impacts children's growth and overall quality of life. Malnutrition and anemia are frequently observed complications that contribute to increased morbidity in children with SCD. Methods: A cross-sectional study was conducted at a tertiary healthcare center in Central India. A total of 194 children aged 5 to 12 years, diagnosed with HbSS sickle cell disease, were selected through convenience sampling. Data were collected using a semi-structured interview schedule conducted during the specialized sickle cell OPD held every Tuesday. Results: In this study involving 194 children with sickle cell disease, 29.9% were underweight, with a higher proportion among females. Normal BMI was observed in 64.9%, while only 5.2% were overweight, and none were obese. Moderate anemia was present in 73.2% and severe anemia in 26.8%, with a mean hemoglobin of 8.43 g/dl. In terms of quality of life (QoL), most children showed excellent emotional (97.4%) and social functioning (100%), while physical (74.2%) and school domains (67%) were relatively lower but still positive. Conclusions: The study highlights that despite a high prevalence of anemia and undernutrition, children with sickle cell disease demonstrate strong emotional and social quality of life. However, their physical health and academic performance are modestly affected, indicating the need for targeted nutritional and educational interventions to enhance overall well-being.